Composite material based on MOFs, self-lubricating fabric composite material and preparation method and application thereof

By using MOFs-based composites in self-lubricated fabric composites, combining Cu-MOFs and phase change materials, the problem of limited tribological properties of existing self-lubricated fabric composites is solved, and higher tribological properties and longer service life is achieved.

CN119859926AActive Publication Date: 2025-04-22LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510151298.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-22
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

The existing self-lubricated fabric composites have limited tribological properties under harsh environments, making it difficult to meet the increasingly high equipment performance requirements.

Method used

Using a composite material based on MOFs, the self-lubricating and thermal stability improvement is achieved by combining Cu-MOFs on the microcapsules and using a combined structure of phase change material and titanium dioxide capsule wall.

Benefits of technology

The tribological properties of self-lubricated fabric composites are significantly improved and the service life of their lubricating components is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859926A_ABST
    Figure CN119859926A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lubricating materials, and provides a composite material based on MOFs, a self-lubricating fabric composite material and a preparation method and application thereof. According to the MOFs-based composite material provided by the invention, the phase-change material can be continuously released under the action of friction stress so as to realize self-lubrication; the titanium dioxide with high thermal conductivity is beneficial to improving the thermal stability of the self-lubricating fabric composite material. Cu-MOFs not only shows excellent lubricating performance, but also reduces the influence of large-size microcapsules on the self-lubricating fabric composite material. The MOFs-based composite material is used as a reinforcing material to modify a self-lubricating fabric composite material, nano-scale flexible Cu-MOFs and a large-size microcapsule are combined to form a micro-nano structure capsule, and the tribological performance of the self-lubricating fabric composite material is remarkably enhanced by utilizing the complementary enhancement effect of the nano-scale flexible Cu-MOFs and the large-size microcapsule; therefore, the service life of the part with the self-lubricating fabric composite material as the lubricating layer is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lubricating materials, and in particular to a composite material and a self-lubricating fabric composite material based on MOFs, and a preparation method and application thereof. Background Art

[0002] Friction is the most basic phenomenon in human life, and the resulting wear seriously affects the operational reliability and life of large industrial equipment. The development of self-lubricating materials has become an effective way to solve this problem. It does not require external lubricants during operation and can provide continuous lubrication by itself. Among them, self-lubricating fabric composites have the advantages of high modulus, high strength and wear resistance, and play an important role in many fields such as aerospace, water conservancy ships and weapons and equipment. Although self-lubricating fabric composites have been widely used, the improvement of self-lubricating fabric composites has been booming due to the increasingly harsh service environment and the continuous improvement of equipment performance requirements.

[0003] Studies have shown that there are three main ways to improve self-lubricating fabric composites: regulating the fabric fabric structure, enhancing the fiber-resin interface performance, and adding functional reinforcement materials. Among them, adding functional reinforcement materials is the most popular modification method. Metal organic frameworks (MOFs) are a type of porous crystalline material formed by self-assembly of metal ions or metal clusters and organic ligands through coordination. MOFs have the advantages of adjustable shape, large specific surface area, good thermal stability and easy shearing, and have been successfully used to enhance the tribological properties of composites. However, the effect of adding MOFs on improving the tribological properties of self-lubricating fabric composites is limited. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a composite material based on MOFs and a self-lubricating fabric composite material and a preparation method and application thereof. The composite material based on MOFs provided by the present invention can greatly improve the tribological properties of the self-lubricating fabric composite material.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a composite material based on MOFs, comprising microcapsules, and MOFs bound to the microcapsules;

[0007] The microcapsule comprises a capsule core and a capsule wall wrapping the capsule core;

[0008] The capsule core is a phase change material, the capsule wall is titanium dioxide, and the MOFs are Cu-MOFs.

[0009] Preferably, the phase change material includes one or more of n-docosane, eicosane, octadecane and hexadecane, and the thickness of the capsule wall is 50-200 nm.

[0010] Preferably, the Cu-MOFs have a two-dimensional layered structure.

[0011] Preferably, the Cu-MOFs are bound to the microcapsules through electrostatic interactions, the microcapsules are positively charged, and the Cu-MOFs are negatively charged.

[0012] The present invention also provides a method for preparing the MOFs-based composite material described in the above technical solution, comprising the following steps:

[0013] Mixing a phase change material, an emulsifier and an organic solvent, and emulsifying the mixture to obtain an oil-in-water emulsion;

[0014] The oil-in-water emulsion and the titanium dioxide precursor are mixed to perform a pre-reaction, and after the pre-reaction is completed, acetic acid and a mixed solvent are sequentially added to the obtained reaction system to perform hydrolysis to obtain microcapsules;

[0015] After the microcapsules and cationic electrolytes are mixed, Cu-MOFs are added to the obtained mixed system for self-assembly to obtain the MOFs-based composite material.

[0016] Preferably, the preparation method of Cu-MOFs comprises the following steps:

[0017] dissolving a soluble copper salt to obtain a copper salt solution;

[0018] The copper salt solution and the organic ligand are mixed and subjected to a hydrothermal reaction to obtain the Cu-MOFs;

[0019] The organic ligand includes terephthalic acid.

[0020] The present invention also provides a self-lubricating fabric composite material, comprising the MOFs-based composite material described in the above technical solution or the MOFs-based composite material prepared by the preparation method described in the above technical solution.

[0021] The present invention also provides a method for preparing the self-lubricating fabric composite material described in the above technical solution, comprising the following steps:

[0022] dispersing the MOFs-based composite material in a resin solution to obtain an impregnation solution;

[0023] The fabric is immersed in the impregnation liquid, taken out, and then hot-pressed and cured in sequence to obtain the self-lubricating fabric composite material.

[0024] Preferably, the mass of the MOFs-based composite material is 0.8-10% of the mass of the resin in the resin solution.

[0025] The present invention also provides the use of the MOFs-based composite material described in the above technical solution or the self-lubricating fabric composite material described in the above technical solution in a lubrication system.

[0026] The present invention provides a composite material based on MOFs, comprising a microcapsule and MOFs combined on the microcapsule; the microcapsule comprises a capsule core and a capsule wall wrapping the capsule core; the capsule core is a phase change material, the capsule wall is titanium dioxide, and the MOFs are Cu-MOFs.

[0027] The MOFs-based composite material provided by the present invention has a phase change material that can continuously release friction stress to achieve self-lubrication; titanium dioxide with high thermal conductivity helps to improve the thermal stability of the self-lubricating fabric composite material. Cu-MOFs not only exhibits excellent lubrication performance, but also reduces the impact of large-sized microcapsules on the self-lubricating fabric composite material. The MOFs-based composite material of the present invention is used as a reinforcing material to modify the self-lubricating fabric composite material, and nano-scale flexible Cu-MOFs and large-sized microcapsules are combined to form micro-nano structure capsules. The tribological properties of the self-lubricating fabric composite material are significantly enhanced by their complementary reinforcement effect, thereby extending the service life of the self-lubricating fabric composite material as a component of the lubricating layer.

[0028] The present invention also provides a method for preparing the composite material based on MOFs described in the above technical solution. The preparation method of the present invention synthesizes a phase change microcapsule based on a phase change material as a capsule core and titanium dioxide as a capsule wall through interfacial condensation polymerization; after the microcapsule is formed, a layer of Cu-MOFs is fixed on the surface of the phase change microcapsule through electrostatic self-assembly to obtain a composite material based on MOFs. The preparation method provided by the present invention is simple to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 TEM photos of Cu-MOFs (a) obtained in Comparative Example 2, TiO2-MePCM (b) obtained in Comparative Example 3, and Cu-MOFs@TiO2-MePCM (c) obtained in Example 1;

[0030] Figure 2 XRD spectra of Cu-MOFs obtained in Comparative Example 2, TiO2-MePCM obtained in Comparative Example 3, Cu-MOFs@TiO2-MePCM obtained in Example 1, and n-docosane;

[0031] Figure 3The graphs are the wear rate (a) and average friction coefficient (b) of the self-lubricating fabric composite materials obtained in Example 1 and Comparative Examples 1 to 3;

[0032] Figure 4 These are SEM photos of the worn surfaces of the self-lubricating fabric composite material (a) obtained in Comparative Example 1 and the self-lubricating fabric composite material (b) obtained in Example 1. DETAILED DESCRIPTION

[0033] The present invention provides a composite material based on MOFs, comprising microcapsules, and MOFs bound to the microcapsules;

[0034] The microcapsule comprises a capsule core and a capsule wall wrapping the capsule core;

[0035] The capsule core is a phase change material, the capsule wall is titanium dioxide, and the MOFs are Cu-MOFs.

[0036] The MOFs-based composite material provided by the present invention includes a microcapsule, wherein the microcapsule includes a capsule core and a capsule wall that wraps the capsule core. In the present invention, the phase change material preferably includes one or more of n-docosane, eicosane, octadecane and hexadecane, and n-docosane is further preferred. In the present invention, the capsule wall is titanium dioxide, and the thickness of the capsule wall is preferably 50 to 200 nm. In the present invention, the particle size of the microcapsule is preferably 1.4 to 3 μm.

[0037] The MOFs-based composite material provided by the present invention includes MOFs bonded to the microcapsule, wherein the MOFs are Cu-MOFs, and the Cu-MOFs refer to MOFs whose inorganic metal center is Cu. In the present invention, copper is a relatively soft metal compared to other metals, and has good thermal conductivity and ductility. The use of Cu-MOFs can improve the lubricity of the material. In the present invention, the Cu-MOFs preferably have a two-dimensional layered structure. In the present invention, the Cu-MOFs with a two-dimensional layered structure are more conducive to improving lubrication performance. Cu-MOFs not only exhibit excellent lubrication performance, but also reduce the influence of large-size microcapsules on the performance of the composite material.

[0038] In the present invention, the Cu-MOFs are preferably bound to the microcapsules through electrostatic interactions, the microcapsules are preferably positively charged, and the Cu-MOFs are preferably negatively charged.

[0039] The present invention also provides a method for preparing the MOFs-based composite material described in the above technical solution, comprising the following steps:

[0040] Mixing a phase change material, an emulsifier and an organic solvent, and emulsifying the mixture to obtain an oil-in-water emulsion;

[0041] The oil-in-water emulsion and the titanium dioxide precursor are mixed to perform a pre-reaction, and after the pre-reaction is completed, acetic acid and a mixed solvent are sequentially added to the obtained reaction system to perform hydrolysis to obtain microcapsules;

[0042] After the microcapsules and cationic electrolytes are mixed, Cu-MOFs are added to the obtained mixed system for self-assembly to obtain the MOFs-based composite material.

[0043] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.

[0044] The present invention mixes a phase change material, an emulsifier and an organic solvent, and emulsifies the mixture to obtain an oil-in-water emulsion.

[0045] In the present invention, the emulsifier preferably includes one or more of sodium dodecyl sulfate (SDS), sodium dodecylbenzene sulfonate, polyethylene glycol ether and Tween 80, and more preferably sodium dodecyl sulfate. In the present invention, the organic solvent is preferably an amide, and the amide is preferably one or more of formamide, acetamide and N,N-dimethylformamide, and more preferably formamide.

[0046] In the present invention, the mass ratio of the phase change material to the emulsifier is preferably 2-12:2-12, more preferably 2-12:2-5, and specifically preferably 5:3.3. In the present invention, the amount ratio of the phase change material to the organic solvent is preferably 2-12g:40-120mL, more preferably 2-12g:50-100mL, and specifically preferably 5g:70mL.

[0047] In the present invention, the emulsification temperature is preferably 30-60°C, specifically preferably 30°C, 40°C, 50°C, 55°C or 60°C; the emulsification is preferably carried out under stirring (referred to as the first stirring), and the rotation speed of the first stirring is preferably 200-800rpm, specifically preferably 200rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 750rpm or 800rpm; the emulsification time is preferably 1-6h, specifically preferably 1h, 2h, 3h, 4h, 5h or 6h.

[0048] In the present invention, the emulsification can form a stable oil-in-water (O / W) emulsion.

[0049] After the emulsification, the oil-in-water emulsion is preferably obtained directly without any treatment.

[0050] After obtaining the oil-in-water emulsion, the present invention mixes the oil-in-water emulsion and a titanium dioxide precursor for a preliminary reaction. After the preliminary reaction is completed, acetic acid and a mixed solvent are sequentially added to the obtained reaction system for hydrolysis to obtain microcapsules.

[0051] In the present invention, the titanium dioxide precursor preferably includes one or more of tetrabutyl titanate (TBT), isopropyl titanate, titanium tetrachloride and titanium trichloride, and more preferably TBT. In the present invention, the amount ratio of the phase change material to the titanium dioxide precursor is preferably 2-12 g:2-12 mL, more preferably 5-10 g:5-10 mL, and more preferably 5 g:5 mL.

[0052] In the present invention, the mixing of the oil-in-water emulsion and the titanium dioxide precursor preferably comprises the following steps: adding the titanium dioxide precursor to the oil-in-water emulsion.

[0053] In the present invention, the temperature of the pre-reaction is preferably 30-60°C, specifically preferably 30°C, 40°C, 50°C, 55°C or 60°C; the pre-reaction is preferably carried out under stirring (referred to as the second stirring), and the rotation speed of the second stirring is preferably 200-800rpm, specifically preferably 200rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 750rpm or 800rpm; the time of the pre-reaction is preferably 0.2-4h, specifically preferably 0.2h, 0.5h, 50min, 1h, 2h, 3h or 4h.

[0054] In the present invention, during the pre-reaction process, the titanium dioxide precursor forms a stable shell layer on the surface of the droplet through electrostatic interaction.

[0055] In the present invention, the usage ratio of the acetic acid to the titanium dioxide precursor is preferably 0.04-0.4g:2-12mL, more preferably 0.04-0.4g:5-10mL, and more preferably 0.1g:5mL. After the acetic acid is added, the present invention preferably performs stirring (referred to as the third stirring), and the time of the third stirring is preferably 4-20min, more preferably 4min, 5min, 10min, 15min or 20min; the acetic acid is to prevent the hydrolysis rate of the titanium dioxide precursor from being too fast.

[0056] In the present invention, the mixed solvent preferably includes water and formamide, the water is preferably deionized water, the amount ratio of water to formamide in the mixed solvent is preferably 2-8g:20-80mL, more preferably 4-6g:20-50mL, and specifically preferably 5g:30mL; the amount ratio of water in the titanium dioxide precursor and the mixed solvent is preferably 2-12mL:2-8g, more preferably 5-10mL:4-6g, and specifically preferably 5mL:5g. In the present invention, the mixed solvent is preferably added dropwise.

[0057] In the present invention, the hydrolysis temperature is preferably 30-60°C, specifically preferably 30°C, 40°C, 50°C or 60°C; the hydrolysis is preferably carried out under stirring (referred to as the fourth stirring), and the rotation speed of the fourth stirring is preferably 200-800rpm, specifically preferably 200rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm or 800rpm; the hydrolysis time is preferably 1-6h, specifically preferably 1h, 2h, 3h, 4h, 5h or 6h.

[0058] After the hydrolysis is completed, the present invention preferably further comprises: filtering the obtained hydrolysis liquid to obtain a filter residue; vacuum drying the filter residue to obtain the microcapsules. In the present invention, washing is preferably performed during the filtering process, and the washing reagent preferably includes water and anhydrous ethanol, and the water is preferably deionized water. In the present invention, the temperature of the vacuum drying is preferably 40°C and the time is preferably 20 hours. In the present invention, the hydrolysis can hydrolyze the titanium dioxide precursor to form titanium dioxide, even if the titanium dioxide wraps the phase change material to form microcapsules.

[0059] After obtaining the microcapsules, the present invention mixes the microcapsules with cationic electrolytes, and then adds Cu-MOFs to the obtained mixed system for self-assembly to obtain the MOFs-based composite material.

[0060] In the present invention, the cationic electrolyte preferably includes one or more of polydiallyldimethylammonium chloride (PDDA), polyethyleneimine and polyvinylamide, and more preferably PDDA. In the present invention, the cationic electrolyte is preferably present in the form of a cationic electrolyte solution, and the concentration of the cationic electrolyte solution is preferably 0.2-2wt%, more preferably 0.5-1.5wt%, and particularly preferably 1wt%; the solvent of the cationic electrolyte solution is preferably a water-N,N-dimethylformamide system, and the volume ratio of water and N,N-dimethylformamide in the water-N,N-dimethylformamide system is preferably 20-100:20-100, more preferably 40-80:40-80, and more preferably 60:60.

[0061] In the present invention, the mass ratio of the microcapsules to the cationic electrolyte is preferably 0.2-2 g:0.8-4 g, and specifically preferably 0.5 g:1.2 g.

[0062] In the present invention, the microcapsules and cationic electrolytes are preferably mixed under ultrasonic conditions, and the ultrasonic time is preferably 2 to 10 minutes, specifically preferably 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes. In the present invention, the cationic electrolyte makes the microcapsules positively charged.

[0063] In the present invention, the mass ratio of the microcapsules to the Cu-MOFs is preferably 0.2-2:0.08-2, more preferably 0.5-1:0.1-1, and particularly preferably 0.5:0.2.

[0064] In the present invention, the preparation method of the Cu-MOFs comprises the following steps:

[0065] dissolving a soluble copper salt to obtain a copper salt solution;

[0066] The copper salt solution and the organic ligand are mixed and subjected to a hydrothermal reaction to obtain the Cu-MOFs;

[0067] The organic ligand includes terephthalic acid.

[0068] In the present invention, the soluble copper salt preferably includes one or more of copper nitrate, copper sulfate and copper chloride, and is more preferably copper nitrate. In a specific embodiment of the present invention, the soluble copper salt is more preferably Cu(NO3)2·3H2O. In the present invention, the dissolving solvent is preferably an organic solvent, and is more preferably N,N-dimethylformamide (DMF).

[0069] In the present invention, the usage ratio of the soluble copper salt to the dissolved solvent is preferably 0.001-0.01 mol:40-100 mL, more preferably 0.0015-0.005:50-80 mL, and particularly preferably 0.0018 mol:60 mL.

[0070] In the present invention, the dissolution temperature is preferably 24-50°C, specifically preferably 24°C, 25°C, 30°C, 35°C, 40°C, 45°C or 50°C; the time is preferably 2-8h, specifically preferably 2h, 3h, 4h, 5h, 6h, 7h or 8h; the dissolution is preferably carried out under stirring conditions.

[0071] In the present invention, the concentration of the copper salt solution is preferably 0.01-0.1 mol / L, specifically preferably 0.01 mol / L, 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L or 0.1 mol / L.

[0072] After obtaining the copper salt solution, the present invention mixes the copper salt solution and the organic ligand, and performs a hydrothermal reaction to obtain the Cu-MOFs.

[0073] In the present invention, the organic ligand comprises terephthalic acid (H2BDC). In the present invention, the molar ratio of the organic ligand to the soluble copper salt is preferably 1:1.

[0074] In the present invention, the copper salt solution and the organic ligand are preferably mixed under ultrasonic treatment, and the ultrasonic treatment time is preferably 0.6 to 4 h, specifically preferably 0.6 h, 1 h, 2 h, 3 h or 4 h.

[0075] In the present invention, the temperature of the hydrothermal reaction is preferably 80-200°C, and specifically preferably 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C; the time of the hydrothermal reaction is preferably 16-30h, and specifically preferably 16h, 18h, 20h, 21h, 22h, 24h, 26h, 28h or 30h. In the present invention, the hydrothermal reaction is preferably carried out in a hydrothermal kettle.

[0076] After the hydrothermal reaction is completed, the present invention preferably further comprises: cooling the obtained hydrothermal reaction liquid to room temperature, filtering to obtain a filter residue; washing and drying the filter residue in sequence to obtain the Cu-MOFs. In the present invention, the washing reagent is preferably N,N-dimethylformamide (DMF). In the present invention, the drying temperature is preferably 60°C, the time is preferably 12h, and the drying is preferably carried out in a vacuum oven.

[0077] In the present invention, the concentration of the copper salt solution is controlled to be 0.01-0.1 mol / L; at the same time, the molar ratio of the organic ligand to the soluble copper salt is controlled to be 1:1, and a two-dimensional layered Cu-MOFs is obtained, which is more suitable for friction. In the present invention, terephthalic acid is used as an organic ligand, and the prepared Cu-MOFs have a negative charge.

[0078] In the present invention, the temperature of the self-assembly is preferably 24-50°C, specifically preferably 24°C, 25°C, 30°C, 35°C, 40°C, 45°C or 50°C; the time is preferably 1-8h, specifically preferably 1h, 2h, 3h, 4h, 5h, 6h, 7h or 8h; the self-assembly is preferably carried out under stirring conditions.

[0079] After the self-assembly, the present invention preferably further comprises: centrifuging the obtained self-assembly liquid to collect the solid; washing and drying the solid in sequence to obtain the MOFs-based composite material. In the present invention, the centrifugal speed is preferably 4000-8000rpm, and specifically preferably 4000rpm, 5000rpm, 6000rpm, 7000rpm or 8000rpm. In the present invention, the washing reagent preferably comprises ethanol and deionized water. In the present invention, the drying is preferably vacuum drying, and the vacuum drying temperature is preferably 30-60°C, and specifically preferably 30°C, 40°C, 50°C or 60°C.

[0080] The present invention also provides a self-lubricating fabric composite material, comprising the MOFs-based composite material described in the above technical solution or the MOFs-based composite material prepared by the preparation method described in the above technical solution.

[0081] In the present invention, the MOFs-based composite material is used as a functional material to improve the tribological properties of the self-lubricating fabric composite material, thereby extending the service life of the component in which the self-lubricating fabric composite material is used as a lubricating layer.

[0082] The present invention also provides a method for preparing the self-lubricating fabric composite material described in the above technical solution, comprising the following steps:

[0083] dispersing the MOFs-based composite material in a resin solution to obtain an impregnation solution;

[0084] The fabric is immersed in the impregnation liquid, taken out, and then hot-pressed and cured in sequence to obtain the self-lubricating fabric composite material.

[0085] The present invention disperses the MOFs-based composite material in a resin solution to obtain an impregnation solution.

[0086] In the present invention, the mass content of the resin in the resin solution is preferably 4-20%, specifically preferably 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%. In the present invention, the resin in the resin solution is preferably one or more of phenolic resin, polyimide resin, epoxy resin and polyamide-imide.

[0087] In the present invention, the mass of the MOFs-based composite material is 0.8-10% of the mass of the resin in the resin solution, and specifically preferably 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0088] After obtaining the impregnation liquid, the present invention immerses the fabric in the impregnation liquid, takes it out, and then performs hot pressing molding and curing in sequence to obtain the self-lubricating fabric composite material.

[0089] In the present invention, the fabric is preferably a PPS / PTFE self-lubricating fabric. In the present invention, the weft yarn of the PPS / PTFE self-lubricating fabric is PPS fiber, and the warp yarn is PTFE fiber; the reinforcing fiber of the PPS / PTFE self-lubricating fabric is PPS fiber, and the lubricating fiber is PTFE fiber. In the present invention, the organization structure of the PPS / PTFE self-lubricating fabric is preferably plain, twill or satin, or one of the evolution structures of the above three original organization structures. In the present invention, the warp density of the PPS / PTFE self-lubricating fabric is preferably 240 to 400 strands / cm, specifically 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, / cm, 390 roots / cm or 400 roots / cm; the weft density is preferably 220-360 roots / cm, specifically 220 roots / cm, 230 roots / cm, 240 roots / cm, 250 roots / cm, 260 roots / cm, 270 roots / cm, 280 roots / cm, 290 roots / cm, 300 roots / cm, 310 roots / cm, 320 roots / cm, 330 roots / cm, 340 roots / cm, 350 roots / cm or 360 roots / cm.

[0090] In the present invention, the fabric is preferably pretreated before use, and the pretreatment preferably includes: desizing, washing and drying in sequence. The present invention does not specifically limit the washing, as long as the oil on the fiber surface can be washed.

[0091] In the present invention, the impregnation is preferably repeated impregnation. After each impregnation, the present invention preferably takes out the impregnated fabric and dries it. The drying temperature is preferably 30 to 80°C, and specifically preferably 30°C, 40°C, 50°C, 60°C, 70°C or 80°C. The drying is preferably carried out in an oven. Each drying preferably also includes weighing and calculating to obtain the weight gain of the resin in the fabric. The present invention does not specifically limit the number of repeated impregnations, and the fabric can be impregnated until the mass fraction of the fabric in the composite material of the fabric and the resin reaches 40 to 85%.

[0092] The present invention does not specifically limit the operation of the hot pressing forming, and those skilled in the art can make settings according to actual needs.

[0093] In the present invention, the curing temperature is preferably 100-240°C, specifically preferably 100°C, 120°C, 140°C, 150°C, 160°C, 180°C, 184°C, 200°C, 220°C or 240°C; the curing pressure is preferably 0.2-2MPa, specifically preferably 0.2MPa, 0.5MPa, 0.8MPa, 1MPa, 1.5MPa or 2MPa; the time is preferably 80-260min, specifically preferably 80min, 100min, 120min, 140min, 150min, 160min, 180min, 200min, 210min, 220min, 240min or 260min. In the present invention, the heating rate to the curing temperature is preferably 6 to 20°C / min, specifically preferably 6°C / min, 8°C / min, 10°C / min, 12°C / min, 14°C / min, 16°C / min, 18°C / min or 20°C / min.

[0094] The present invention also provides the use of the MOFs-based composite material described in the above technical solution or the self-lubricating fabric composite material described in the above technical solution in a lubrication system.

[0095] The present invention does not specifically limit the application of the MOFs-based composite material or the self-lubricating fabric composite material described in the above technical solution, and those skilled in the art can make settings according to actual needs.

[0096] The MOFs-based composite material and self-lubricating fabric composite material provided by the present invention and their preparation methods and applications are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0097] Comparative Example 1

[0098] (1) PPS fiber and PTFE fiber are used to weave PPS / PTFE self-lubricating fabric (twill structure, warp density of 320 strands / cm, weft density of 290 strands / cm), which is then desized and cleaned with fiber surface oil and then dried for use.

[0099] (2) The PPS / PTFE self-lubricating fabric grey cloth was repeatedly immersed in a phenolic resin solution (the mass content of the phenolic resin was 15%) until the mass fraction of the fabric in the fabric and resin composite material reached 75±5wt% to obtain an uncured self-lubricating fabric composite material, which was bonded to the surface of a metal substrate using a phenolic resin adhesive and cured at 0.8 MPa and 184°C for 2 h to obtain a nationally produced self-lubricating fabric composite test piece, which was recorded as Pure FC.

[0100] The friction and wear performance of the self-lubricating fabric composite material was evaluated by using the Xuanwu No. 3 friction and wear tester. The contact mode was pin-disc. At room temperature, the dynamic load was 45 MPa, the rotation speed was 0.3 m / s, and the friction test was 2 h. The results showed that the average friction coefficient and wear rate of the self-lubricating fabric composite material were 0.053 and 5.94×10 -14 m 3 / N·m.

[0101] Comparative Example 2

[0102] (1) PPS fiber and PTFE fiber are used to weave PPS / PTFE self-lubricating fabric (twill structure, warp density of 320 strands / cm, weft density of 290 strands / cm), which is then desized and cleaned with fiber surface oil and then dried for use.

[0103] (2) When the organic ligand and soluble copper salt are adjusted to an appropriate concentration in the solvent, two-dimensional layered MOFs can be synthesized by a one-step hydrothermal method. Cu(NO3)2·3H2O (0.0018 mol) was added to DMF (60 mL) and stirred at 30°C for 4 h to obtain a uniform blue copper salt solution. Then, terephthalic acid H2BDC was added to the copper salt solution in the same molar amount as copper nitrate and ultrasonically treated for 1 h. Then, the resulting mixed system was placed in a hydrothermal reactor and hydrothermally reacted at 120°C for 24 h. After the hydrothermal reaction was completed, it was cooled to room temperature, filtered, and the filter residue was washed 4 times with DMF and dried in a vacuum oven at 60°C for 12 h to obtain Cu-MOFs.

[0104] (3) The PPS / PTFE self-lubricating fabric grey cloth was repeatedly immersed in a phenolic resin solution containing Cu-MOFs (the mass fraction of Cu-MOFs relative to phenolic resin was 2wt%, and the mass content of phenolic resin in the phenolic resin solution was 15%) until the mass fraction of the fabric in the fabric and resin composite material reached 75±5wt%, thereby obtaining an uncured self-lubricating fabric composite material, which was bonded to the surface of a metal substrate using a phenolic resin adhesive and cured at 0.8MPa and 184°C for 2h to obtain a nationally produced self-lubricating fabric composite material test piece, which was recorded as FC-1.

[0105] The friction and wear performance of the self-lubricating fabric composite material was evaluated by using the Xuanwu No. 3 friction and wear tester. The contact mode was pin-disc. At room temperature, the dynamic load was 45 MPa, the rotation speed was 0.3 m / s, and the friction test was 2 h. The results showed that the average friction coefficient and wear rate of the self-lubricating fabric composite material were 0.05 and 4.71×10 -14 m 3 / N·m.

[0106] Comparative Example 3

[0107] (1) PPS fiber and PTFE fiber are used to weave PPS / PTFE self-lubricating fabric (twill structure, warp density of 320 strands / cm, weft density of 290 strands / cm), which is then desized and cleaned with fiber surface oil and then dried for use.

[0108] (2) Phase change microcapsules based on n-docosane core and titanium dioxide wall were synthesized by interfacial polycondensation. 5.0 g of docosane, 70.0 mL of formamide and 3.3 g of SDS were mixed in a closed beaker and stirred at 750 rpm for 2 h at 55 °C to form a stable oil-in-water (O / W) emulsion. Then, 5.0 mL of titanium dioxide precursor TBT was added to the beaker and stirred at 750 rpm for 50 min at 55 °C to form a stable shell on the droplet surface through electrostatic interaction. Subsequently, 0.1 g of acetic acid was added to the emulsion and stirred for 10 min to prevent the hydrolysis rate of TBT from being too fast. Finally, 5.0 g of deionized water and 30.0 mL of formamide mixed solvent were added dropwise to the above reaction system and stirred at 500 rpm for 4 h. After the reaction was completed, the mixture was repeatedly washed with deionized water and anhydrous ethanol during the filtration process and vacuum dried at 40 °C for 20 h to obtain microcapsules, which were recorded as TiO2-MePCM.

[0109] (3) The PPS / PTFE self-lubricating fabric blank was repeatedly immersed in a phenolic resin solution of TiO2-MePCM (the mass fraction of TiO2-MePCM relative to phenolic resin was 2wt%, and the mass fraction of phenolic resin in the phenolic resin solution was 15%) until the mass fraction of the fabric in the fabric and resin composite material reached 75±5wt%, thereby obtaining an uncured self-lubricating fabric composite material. The uncured self-lubricating fabric composite material was bonded to the surface of a metal substrate using a phenolic resin adhesive, and cured at 0.8MPa and 184°C for 2h to obtain a nationally produced self-lubricating fabric composite material test piece, which was recorded as FC-2.

[0110] The friction and wear performance of the self-lubricating fabric composite material was evaluated by using the Xuanwu No. 3 friction and wear tester. The contact mode was pin-disc. At room temperature, the dynamic load was 45 MPa, the rotation speed was 0.3 m / s, and the friction test was 2 h. The results showed that the average friction coefficient and wear rate of the self-lubricating fabric composite material were 0.0491 and 4.12×10 -14 m 3 / N·m.

[0111] Example 1

[0112] (1) PPS fiber and PTFE fiber are used to weave PPS / PTFE self-lubricating fabric (twill structure, warp density of 320 strands / cm, weft density of 290 strands / cm), which is then desized and cleaned with fiber surface oil and then dried for use.

[0113] (2) Cu-MOFs modified TiO2-MePCM was prepared by electrostatic self-assembly. First, 0.5 g of TiO2-MePCM (obtained in Comparative Example 3) was added to a 1 wt% PDDA solution (60 mL of deionized water and 60 mL of DMF, including 1.2 g of PDDA) and ultrasonicated for 5 min. Then, 0.2 g of Cu-MOFs (obtained in Comparative Example 2) was added to the above solution and stirred at 30 ° C for 3 h. After the reaction was completed, centrifuged at 6000 r / min, washed with ethanol and deionized water to remove excess reactants, and vacuum dried at 40 ° C to obtain a MOFs-based composite material, recorded as Cu-MOFs@TiO2-MePCM.

[0114] (3) The PPS / PTFE self-lubricating fabric blank was repeatedly immersed in the phenolic resin solution of Cu-MOFs@TiO2-MePCM (the mass fraction of Cu-MOFs@TiO2-MePCM relative to phenolic resin was 2wt%, and the mass content of phenolic resin in the phenolic resin solution was 15%) until the mass fraction of the fabric in the fabric and resin composite material reached 75±5wt%, and an uncured self-lubricating fabric composite material was obtained. The uncured self-lubricating fabric composite material was bonded to the surface of the metal substrate with a phenolic resin adhesive and cured at 0.8MPa and 184℃ for 2h to obtain a nationally produced self-lubricating fabric composite material test piece, which was recorded as FC-3.

[0115] The friction and wear performance of the self-lubricating fabric composite material was evaluated by using the Xuanwu No. 3 friction and wear tester. The contact mode was pin-disc. At room temperature, the dynamic load was 45 MPa, the rotation speed was 0.3 m / s, and the friction test was 2 h. The results showed that the average friction coefficient and wear rate of the self-lubricating fabric composite material were 0.047 and 2.76×10 -14 m 3 / N·m.

[0116] Figure 1 TEM images of Cu-MOFs (a) obtained in Comparative Example 2, TiO2-MePCM (b) obtained in Comparative Example 3, and Cu-MOFs@TiO2-MePCM (c) obtained in Example 1; Figure 1 It can be seen that: Cu-MOFs has a stacked sheet structure with a very smooth surface, and TiO2-MePCM has a regular spherical morphology without any surface defects. In contrast, the surface of Cu-MOFs@TiO2-MePCM becomes rough and presents a wrinkled crystalline layer, and the two-dimensional layered Cu-MOFs can be clearly seen.

[0117] Figure 2 The XRD spectra of Cu-MOFs obtained in Comparative Example 2, TiO2-MePCM obtained in Comparative Example 3, Cu-MOFs@TiO2-MePCM obtained in Example 1, and n-docosane; Figure 2It can be seen that the characteristic peaks of 10.2°, 12.1°, 17.2°, 20.4° and 24.8° appearing in the spectrum of Cu-MOFs belong to the (110), (001), (-201), (220) and (131) crystal planes, indicating that it has a high degree of crystallinity and a face-centered cubic structure. The spectra of Cu-MOFs@TiO2-MePCM and n-docosane have similar diffraction peaks, which indicates that n-docosane still has a stable crystal structure after layer-by-layer encapsulation and can absorb and release frictional heat. It is worth noting that the diffraction peak of TiO2 cannot be observed in the spectrum because it is in an amorphous state. The above characterization analysis proves that the core-shell structured Cu-MOFs-based composite material has been successfully prepared.

[0118] The friction and wear performance of the self-lubricating fabric composite material was evaluated using the Xuanwu No. 3 friction and wear testing machine. The contact mode was pin-disc, the dynamic load was 45MPa, the rotation speed was 0.3m / s, and the friction test was 2h. The results are as follows Figure 3 As shown, Figure 3 The wear rate (a) and average friction coefficient (b) of the self-lubricating fabric composite material obtained in Example 1 and Comparative Examples 1 to 3 are shown in FIG. Figure 3 As shown in the figure, the wear rate of the pure self-lubricating fabric composite is large, and the direct and dual contact of PTFE fibers reduces the friction coefficient. After adding MePCM, the wear rate of the self-lubricating fabric composite is significantly reduced, and FC-3 with Cu-MOFs@TiO2-MePCM shows the smallest average wear rate and friction coefficient.

[0119] Figure 4 The SEM photos of the wear surfaces of the self-lubricating fabric composite material (a) obtained in Comparative Example 1 and the self-lubricating fabric composite material (b) obtained in Example 1 are shown in FIG. Figure 4 It can be seen that for the pure self-lubricating fabric composite material, a large number of fibers can be pulled out and broken due to severe wear, and the phenolic resin on the wear surface is peeled off. For FC-3 with Cu-MOFs@TiO2-MePCM added, the reinforcing fibers are tightly combined with the resin matrix, the wear surface is quite smooth, and only a few phenolic resins fall off.

[0120] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A composite material based on MOFs, characterized in that: It includes microcapsules, and MOFs bound to the microcapsules; The microcapsule comprises a capsule core and a capsule wall wrapping the capsule core; The capsule core is a phase change material, the capsule wall is titanium dioxide, and the MOFs are Cu-MOFs.

2. The MOFs-based composite material according to claim 1, characterized in that The phase change material includes one or more of n-docosane, eicosane, octadecane and hexadecane, and the thickness of the capsule wall is 50-200 nm.

3. The MOFs-based composite material according to claim 1, characterized in that The Cu-MOFs have a two-dimensional layered structure.

4. The MOFs-based composite material according to claim 1, characterized in that The Cu-MOFs are bound to the microcapsules through electrostatic interactions, the microcapsules are positively charged, and the Cu-MOFs are negatively charged.

5. The method for preparing a composite material based on MOFs according to any one of claims 1 to 4, characterized in that: The following steps are involved: Mixing a phase change material, an emulsifier and an organic solvent, and emulsifying the mixture to obtain an oil-in-water emulsion; The oil-in-water emulsion and the titanium dioxide precursor are mixed to perform a pre-reaction, and after the pre-reaction is completed, acetic acid and a mixed solvent are sequentially added to the obtained reaction system to perform hydrolysis to obtain microcapsules; After the microcapsules and cationic electrolytes are mixed, Cu-MOFs are added to the obtained mixed system for self-assembly to obtain the MOFs-based composite material.

6. The preparation method according to claim 5, characterized in that: The preparation method of the Cu-MOFs comprises the following steps: dissolving a soluble copper salt to obtain a copper salt solution; The copper salt solution and the organic ligand are mixed and subjected to a hydrothermal reaction to obtain the Cu-MOFs; The organic ligand includes terephthalic acid.

7. A self-lubricating fabric composite material, characterized in that: The invention comprises the MOFs-based composite material according to any one of claims 1 to 4 or the MOFs-based composite material prepared by the preparation method according to any one of claims 5 to 6.

8. The method for preparing the self-lubricating fabric composite material according to claim 7, characterized in that: The following steps are involved: dispersing the MOFs-based composite material in a resin solution to obtain an impregnation solution; The fabric is immersed in the impregnation liquid, taken out, and then hot-pressed and cured in sequence to obtain the self-lubricating fabric composite material.

9. The preparation method according to claim 8, characterized in that: The mass of the MOFs-based composite material is 0.8-10% of the mass of the resin in the resin solution.

10. Use of the MOFs-based composite material according to any one of claims 1 to 4 or the self-lubricating fabric composite material according to claim 7 in a lubrication system.

Citation Information

Patent Citations

  • Self-lubricating microcapsule, preparation method thereof and self-lubricating composite material containing self-lubricating microcapsule

    CN116083140A

  • Microcapsule and kaolin composite reinforced self-lubricating fabric liner material and application thereof

    CN117779452A

  • Copper modified titanium dioxide photocatalyst with hierarchical pore structure and preparation method of copper modified titanium dioxide photocatalyst

    CN118403632A

  • Phase change microcapsule with core-shell structure, preparation method of phase change microcapsule and self-lubricating fabric composite material

    CN118895105A